Evaluation of an urban traffic Noise–Exposed population based on points of interest and noise maps: The case of Guangzhou - Wang, Haibo; Chen, Hanjie; Cai, Ming (Environmental pollution (1987), 2018)
The primary objective of this study was to develop an evaluation method for assessing an urban traffic noise–exposed population and apply it in the main urban area of Guangzhou. The method based on points of interest (POIs) and noise map is realized in several steps. First, after regionalizing based on road networks and executing a cluster analysis for regions according to the properties of POIs, the environmental noise functional regions (NFRs) of the urban area are presented. Then, surrounding POIs are used to infer the type of buildings, and according to the attraction of different building types and the whole population of the region, the population distribution at the building level is calculated. Finally, with the help of a noise map, an evaluation method for assessing an urban traffic noise–exposed population is proposed. The method is applied in the main urban area of Guangzhou, and the results reveal the followings. 1) At daytime and nighttime, 23.63% and 30.53% of the population, respectively, experience noise levels that exceed the noise standards. The per capita noise exposure value at daytime and nighttime is 0.9 dB and 2.0 dB, respectively. 2) The percentages of the exposed population of Yuexiu District were 28.89% at daytime and 35.65% at nighttime, which are the largest, followed by the exposed population percentages of Liwan, Haizhu, and Tianhe Districts. 3) From the view of different classes of NFRs, the percentages of the exposed population of Class 1 and Class 4 are larger than the percentages of the exposed population from the other classes, especially at nighttime (48.24% of Class 1 and 40.79% of Class 4). 4) Although there are masses of people affected by traffic noise, a large percentage of them (85%) experience not more than 5 dB of traffic noise superscale. [Display omitted] •Points of interest (POIs) and noise map were applied to evaluate urban traffic noise–exposed population.•High-density areas with residence-relative POIs suffer more serious exposure to noise.•Except for population, daytime or nighttime and noise functional region (NFR) classes also play important roles in the noise effect on humans.•Road-side areas and nighttime, in particular, should be paid attention.